Empirical differentiation of task types - an explorative study - Stuppan, Sebastian; Wilhelm, Markus; Bölsterli Bardy, Katrin (Swiss Journal of Educational Research, 2023)
As attention has shifted over the last decade from input to outcome orientation and from school to teaching quality, researchers have increasingly focused on task quality. To support learners’ cumulative competency development as envisaged by curricula, sets of tasks that build on each other are becoming more important. Using the Learning Process Model presented in this study, tasks can be divided into five types: confrontation, development, exercise, synthesis, and transfer, to promote competency-enhancing education. The extent to which this theoretical assumption of task types is reflected in the task sets is investigated. In this study, 58 STEM tasks were grouped using cluster analysis to identify task types. The results show that a typology of tasks can in principle be derived.